2007
DOI: 10.1080/09638180701507163
|View full text |Cite
|
Sign up to set email alerts
|

XBRL: An (Open) Source of Enlightenment or Disillusion?

Abstract: Extensible Business Reporting Language (XBRL) is being adopted by European regulators as a data standard for the exchange of business information. This paper examines the approach of XBRL International (XII) to the meta-data standard's development and diffusion. We theorise the development of XBRL using concepts drawn from a model of successful open source projects. Comparison of the open source model to XBRL enables us to identify a number of interesting similarities and differences. In common with open sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 50 publications
0
40
0
Order By: Relevance
“…Users want more flexibility, ease of use and timeliness in financial reporting (FASB 2000; CICA Along with all these mandates and calls for the use of XBRL, even more numerous predictions have appeared of the radical impacts its adoption will have on business and the accounting profession (Cohen 2005, Trites 2004, Wagenhofer 2003, Coffin 2001a& 2001b. However, some have suggested that interest in this type of technology is low (Xiao et al 2002) and others have cautioned against overstatement and over hype by XBRL enthusiasts (Locke and Lowe 2007). Unfortunately, these predictions have been supported by little research investigating the probability of future XBRL impacts.…”
Section: Introductionmentioning
confidence: 97%
“…Users want more flexibility, ease of use and timeliness in financial reporting (FASB 2000; CICA Along with all these mandates and calls for the use of XBRL, even more numerous predictions have appeared of the radical impacts its adoption will have on business and the accounting profession (Cohen 2005, Trites 2004, Wagenhofer 2003, Coffin 2001a& 2001b. However, some have suggested that interest in this type of technology is low (Xiao et al 2002) and others have cautioned against overstatement and over hype by XBRL enthusiasts (Locke and Lowe 2007). Unfortunately, these predictions have been supported by little research investigating the probability of future XBRL impacts.…”
Section: Introductionmentioning
confidence: 97%
“…By standardizing the form in which financial data are exchanged, XBRL can integrate information flows within communities of diverse organizations that can generate enormous efficiencies (Deshmukh, 2004;Debreceny, 2007;Locke and Lowe, 2007;Pinsker and Li, 2008). Furthermore, XBRL has the advantage that it is extensible, particularly as it enables the addition of specific features and thus enhances its usability without replacing existing accounting standards (Locke and Lowe, 2007;Boritz and No, 2008). The next section gives an overview of existing theories with regard to the usage and diffusion of XBRL.…”
Section: Theories About Xbrl Adoptionmentioning
confidence: 99%
“…According to the research article from Locke and Lowe (2007), advocacy of individual participants can have a positive effect in achieving the critical mass of diffusion. However, in the example of XBRL, the authors blame highly exaggerated comments such as the claim that XBRL will "have consequences similar to the transition from paper and pencil to the use of spreadsheets" (Covaleski, 2000) with regard to XBRL, which created conflicts and excessively high expectations.…”
Section: Xbrl For Corporate Governance Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Locke and Lowe (2007), the acceptance of taxonomies is a relevant challenge for the successful development and diffusion of XBRL. Debreceny et al (2005) discuss a series of research implications of the development of XBRL taxonomies; specifically, they focus on the completeness of taxonomies, the factors that determine the adequacy of standard taxonomies and the role of extensions in the standard taxonomies.…”
Section: Literature Review Of Xbrl Taxonomiesmentioning
confidence: 99%